Estimation of wastewater and solid waste loading along Estero de Paco - Dagupan, Romar U.; Tanchuling, Maria Antonia N.; Clemente, Eligia D.; Ereneo, Sarah Jane P. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
This study aimed to estimate the solid waste and waste water loading along Estero de Paco. The solid waste loading was estimated based on the daily collection data of the Pasig River Rehabilitation Commission. For the estimation of point source wastewater load, volumetric flow rate of the effluents and its pollutant concentration were obtained. The load contribution of non-point sources was estimated using mass balance analysis for the non-reactive pollutants; while the Streeter-Phelps Model was used to model the DO and BOD loadings from non-point sources. It was found out that the Apacible to UN Avenue had the highest generated solid waste at 56.24 kg/day which were mostly comprised of plastic materials. On the other hand, for waste water, 20.14% of the amount of pollutants were from non-point sources; while the rest were from point sources. Based from the sensitivity analysis, the amount of dissolved oxygen was sensitive to reaeration rate, deoxygenation rate, and BOD settling velocity; while BOD was only sensitive to BOD settling velocity. These results can be made as bases for future policies and programs.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Waste disposal in rivers, lakes, etc. -- Philippines; Estuaries -- Philippines -- Manila